B Cell Receptor Genes Associated With Tolerance Identify a Cohort of Immunosuppressed Patients With Improved Renal Allograft Graft Function. Issue 10 (2nd May 2017) - Asare, A.; Kanaparthi, S.; Lim, N.; Phippard, D.; Vincenti, F.; Friedewald, J.; Pavlakis, M.; Poggio, E.; Heeger, P.; Mannon, R.; Burrell, B. E.; Morrison, Y.; et al.
Abstract : We previously reported that two B cell receptor genes, IGKV1D‐13 and IGKV4‐1, were associated with tolerance following kidney transplantation. To assess the potential utility of this "signature, " we conducted a prospective, multicenter study to determine the frequency of patients predicted tolerant within a cohort of patients deemed to be candidates for immunosuppressive minimization. At any single time point, 25–30% of patients were predicted to be tolerant, while 13.7% consistently displayed the tolerance "signature" over the 2‐year study. We also examined the relationship of the presence of the tolerance "signature" on drug use and graft function. Contrary to expectations, the frequency of predicted tolerance was increased in patients receiving tacrolimus and reduced in those receiving corticosteroids, mycophenolate mofetil, or Thymoglobulin as induction. Surprisingly, patients consistently predicted to be tolerant displayed a statistically and clinically significant improvement in estimated glomerular filtration rate that increased over time following transplantation. These findings indicate that the frequency of patients consistently predicted to be tolerant is sufficiently high to be clinically relevant and confirm recent findings by others that immunosuppressive agents impact putative biomarkers of tolerance. The association of a B cell–based "signature" with graft function suggests that B cells may contribute to the function/survival of transplanted kidneys. Abstract : The authors demonstrate an association between a previously described potential signature of renal allograft tolerance and improved renal allograft function in stable patients on maintenance immunosuppression. See Christakoudi and Hernandez‐Fuentes's editorial on page 2505 .